2-Hydroxy-dATP is incorporated opposite G by Escherichia coli DNA polymerase III resulting in high mutagenicity - Kamiya, Hiroyuki (Oxford University Press, 2000)
Four kinds of oxidatively damaged DNA precursors, 8-hydroxydeoxyguanosine 5′-triphosphate (8-OH-dGTP), 2-hydroxydeoxyadenosine 5′-triphosphate (2-OH-dATP), 5-hydroxydeoxycytidine 5′-triphosphate (5-OH-dCTP) and 5-formyldeoxyuridine 5′-triphosphate (5-CHO-dUTP), were employed in in vitro gap-filling reactions of the supF gene conducted by the Escherichia coli DNA polymerase III holoenzyme, and these treated DNAs were transfected into various E.coli strains. When the manipulated DNAs were transfected into the repair-proficient strain, supF mutants were obtained much more frequently by the purine nucleotides than by the pyrimidine nucleotides (2-OH-dATP > 8-OH-dGTP >> 5-OH-dCTP ~ 5-CHO-dUTP). This result is in contrast to our previous observation that these four oxidatively damaged nucleotides induce chromosomal gene mutations with similar frequencies when incorporated directly into E.coli. 2-OH-dATP elicited G→T transversions, indicating the formation of G•2-OH-dATP pairs. These results demonstrate that 2-OH-dATP was highly mutagenic in this assay system containing the in vitro DNA synthesis by the E.coli replicative DNA polymerase, in addition to in the in vivo assay system reported previously. Slight increases in the mutant frequencies were observed when alkA (for 8-OH-dGTP and 2-OH-dATP) and mutY (for 2-OH-dATP) strains were used as hosts. This is the first report that clearly shows the formation of G•2-OH-dATP pairs.